Numerical and experimental study of air flow by natural convection in a rectangular open cavity: Application in a top refrigerator - Durmus, A.; Daloglu, A. (Taylor & Francis Inc, 2008)
In this study, unsteady-state natural convection in an open rectangular prismatic cavity was examined. Experiments were carried out using a table-top refrigerator for an open-door case in which air flow was promoted by natural convection under two-dimensional laminar and transition flows conditions. Numerical analysis was completed by using computational fluid dynamic (CFD) software. It was assumed that the rectangular prismatic cavity has a vertical opening, a cooled wall at the top, and insulated side walls. Air velocity measurements were completed by using a hot-wire anemometer. Average Nusselt numbers, which were obtained experimentally, were found to be quite close to the numerically calculated values. When the door opens, the average Nusselt number for the cooling surface increases and reaches a steady-state condition as time passes. When the temperature difference was at its maximum value, Rayleigh number was calculated to be 3.2 X 10(8).
Keywords: natural convection; laminar flow; transition flow; open cavity; rectangular cavity; refrigerator